Konsep Perikoresis Allah Tritunggal Menurut Leonardo Boff dan Relevansinya Bagi Kehidupan Berkomunitas Kaum Religius - Dionisius Sunardi; Yulius Defri Sudi (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2026)
This article focuses on an attempt to analyze the relevance of Leonardo Boff’s concept of the perichoresis of the Triune God to the communal life of religious communities. The analysis is conducted using an interpretative-conceptual approach to identify the connection between Trinitarian perichoresis and the dynamics of communal life. This research employs a literature review method, examining Leonardo Boff’s major works as well as supporting literature related to religious community life. The research results indicate that the concept of perichoresis, which emphasizes the mutually permeating relationship within the unity of love between the Father, the Son, and the Holy Spirit, holds significant relevance for the renewal of religious community life. In the light of this concept, the uniqueness of each community member can be acknowledged without undermining unity, whilst equal relationships are maintained despite differences in roles and responsibilities. Furthermore, perichoresis also fosters a spirit of cooperation in ministry as a concrete expression of a living communion. Thus, the concept of perichoresis not only holds theological value but also offers a practical model for a more dialogical, inclusive, and love-based communal life.